Faktor-faktor yang mempengaruhi kecemasan dental pasien usia dewasa muda sebelum tindakan perawatan gigi di Puskesmas II Denpasar Barat - Kadek Kartika Candra Dewi; Putu Ika Anggaraeni; Tience Debora Valentina (School of Dentistry Faculty of Medicine Udayana University, 2018)
Background: Dental anxiety is a general response which will be experienced by a person prior to the act of dental care. Dental anxiety experienced by patients will bring negative effects to patients undergoing dental treatments. Patients who have dental anxiety tend to avoid dental visit regularly and requires more time in dental treatment. Aim: This study aims to know factors that influence anxiety of young adult dental patients before dental treatment at the society health center II West DenpasarMethods: Analytic cross sectional method and consecutive sampling technique were used in this study. Data were collected using a questionnaire namely Short Version of the Dental Anxiety Inventory (S-DAI) to find out the patient’s level of anxiety before undergoes dental treatment. The data was analyzed using Chi-Square test. Processing technique and data analysis was done with statistical test Chi Square. Results: Result showed that H0 was rejected (p<0,05). It is concluded that there was relationship between dental anxiety before dental treatment and gender, age, sosio-economic, and education. Conclusion: Based on the research results, it can be concluded that there is a relationship between the dental anxiety before dental treatment with gender, age, socio-economic, educational and health center II in West Denpasar.